2023
DOI: 10.1002/mdc3.13718
|View full text |Cite
|
Sign up to set email alerts
|

How Is Functional Neurological Disorder Managed in Australian Hospitals? A Multi‐Site Study Conducted on Acute Inpatient and Inpatient Rehabilitation Wards

Abstract: Background Successful management for functional neurological disorder (FND) requires multidisciplinary involvement starting with providing a definitive diagnosis. Objectives To observe clinical management of patients with FND during hospital admission. Methods A prospective observational study was conducted over six Australian hospitals over a 4‐month period. Data collected included patient demographics, communication of the diagnosis of FND, access to the multidisciplinary team, hospital length of stay (LOS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A UK study confrmed that non-coding is very common in FND [17]. In Australia, a prospective observational study by Petrie and colleagues [18] found that 89% of inpatients managed on nonneurosciences wards did not have a diagnosis communicated and 58% did not have it documented. Tese challenges may result from the reluctance to provide a formal diagnosis, FND being wrongly viewed as a diagnosis of exclusion, and poor knowledge of FND among non-neurology teams.…”
Section: Discussionmentioning
confidence: 99%
“…A UK study confrmed that non-coding is very common in FND [17]. In Australia, a prospective observational study by Petrie and colleagues [18] found that 89% of inpatients managed on nonneurosciences wards did not have a diagnosis communicated and 58% did not have it documented. Tese challenges may result from the reluctance to provide a formal diagnosis, FND being wrongly viewed as a diagnosis of exclusion, and poor knowledge of FND among non-neurology teams.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple efforts have been made to improve outcomes for patients with FNSDs, including (1) enhancements to medical education (Barnett et al, 2022;Rawlings & Reuber, 2018), (2) guidelines for communication with patients (Finkelstein et al, 2022;Rockliffe-Fidler & Willis, 2019), (3) the development of evidence-based psychotherapeutic interventions (Goldstein et al, 2020;LaFrance et al, 2014), and (4) increased interdisciplinary care (Lidstone et al, 2020;Petrie et al, 2023). Items 1 and 4 are expanded upon below because of their relevance to neuropsychologists.…”
Section: Advancements In Management and Treatmentmentioning
confidence: 99%